An Antifouling Photoelectrochemical Ultramicrosensor for Unbiased Single‐Cell Analysis. Issue 4 (24th December 2021) - Zhu, Linlin; Zhong, Lin; Wang, Juan; Tang, Ying; Liu, Zhihong
Comprehensive Summary: The nanoelectrode‐based electrochemical method has been widely used for single‐cell analysis because of the advantages of high spatiotemporal resolution and in‐situ detection capability. As an evolutional generation of the electrochemical analysis, photoelectrochemical (PEC) sensors not only inherit the above‐mentioned merits, but also possess a lower background and higher sensitivity, because they can operate under unbiased conditions. Moreover, electrodes are often impaired by nonspecific binding in complex biological environments. Thus, an antifouling PEC ultramicrosensor is developed for unbiased single‐cell analysis in this report. The ultramicrosensor is fabricated by self‐assembling of photoactive material ZnCaInS nanosheets onto the carbon fiber ultramicroelectrode surface and further dip‐coating of a porous antifouling layer of cross‐linked bovine serum albumin supported by carbon nanotubes. Benefiting from the minimal influence of the ultrathin nanosheet on the ultramicroelectrode morphology and the smooth protective interface formed by the antifouling film, the obtained photoelectrode can be readily inserted into a single cell with negligible impact on cell viability and shows excellent antifouling performance. The PEC ultramicrosensor achieves selective detection of dopamine (DA) with a low detection limit (3.97 nmol/L) and exhibits good sensing capability for cytosolic DA in single PC12 cells. This exploration provides new opportunities for single‐cell analysis. Abstract : An antifouling photoelectrochemical ultramicrosensor was demonstrated for unbiased single‐cell analysis, which not only inherits the high spatiotemporal resolution and in‐situ detection capability of electrochemical methods, but also possesses low background and high sensitivity. This sensor exhibits excellent antifouling performance and good sensing ability for cytosolic DA in single PC12 cells.